The Influence of Understanding Financial Literacy and Community Readiness on the Use of Central Bank Digital Currency (CBDC) - Amarta, Cindy Cintania; Latifah, Fitri Nur (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
The purpose of this study was to analyze the influence of public understanding of financial literacy and community readiness on the use of Central Bank Digital Currency (CBDC). This is expected to provide information on public knowledge regarding readiness in facing challenges of use (CBDC). This research method uses a quantitative approach. Data collection was carried out by distributing questionnaires. There are 100 research samples with sample criteria, namely the millennial generation born in 1986-1995 and the Z generation from 1996-2005. Researchers used a Likert scale to determine the value of respondents' answers. After that, the data obtained were then analyzed using tools, namely SPSS software by conducting instrument quality tests, validity and reliability tests, classical assumption tests, normality tests, heteroscedasticity tests, multicollinearity tests, and hypothesis testing. t-test and f-test, and test the coefficient of determination. The results of this study indicate that there is a positive relationship between the variables of understanding financial literacy and community readiness for the use of Central Bank Digital Currency (CBDC).